2008
DOI: 10.1097/01.aog.0000296715.07705.e9
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Subtypes in Ovarian Cancer

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 13 publications
7
75
2
1
Order By: Relevance
“…As hormone-sensitive cancer, a large subset of ovarian cancers is associated with the deregulation of ERα or AR (Rao et al, 1991;Chan et al, 2008). Our study demonstrated that ATAD2 is overexpressed in ovarian cancers.…”
Section: Discussionmentioning
confidence: 54%
“…As hormone-sensitive cancer, a large subset of ovarian cancers is associated with the deregulation of ERα or AR (Rao et al, 1991;Chan et al, 2008). Our study demonstrated that ATAD2 is overexpressed in ovarian cancers.…”
Section: Discussionmentioning
confidence: 54%
“…Two groups have investigated ER expression on the RNA level using fresh frozen ovarian tumor tissue. Chan et al (2008) found a prognostic impact of ESR2 but not ESR1 mRNA expression; however, the significance of these results is limited by the fact that epithelial and non-epithelial malignant ovarian tumors as well as borderline tumors were evaluated together. Fujimoto et al (2000) found the ratio ESR2 to ESR1 mRNA to be prognostic for ovarian cancer patients but did not evaluate ER mRNA expression quantitatively and used a very small sample size (28 patients) for the analysis.…”
Section: Discussionmentioning
confidence: 78%
“…These initial findings had not taken into account the presence of ER subtypes. Both ERa and ERb were found to be present in both normal ovarian tissues and ovarian cancer tissues, with a possible reduction of ERb expression as tumors progress (Bardin et al 2004a, Chan et al 2008. The loss of ERb expression indicates that ERb exerts tumor-suppressive functions and may have a protective role.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, ERb has been found in most estrogen-target tissues such as the prostate (Weihua et al 2001) and the ovary (Brandenberger et al 1998). Reduced levels of ERb mRNA expression were found in malignant tissues compared with normal tissues in various estrogendependent tumors such as breast, prostate, and ovarian cancers (Iwao et al 2000, Horvath et al 2001, Skliris et al 2003, Chan et al 2008, indicating that the loss of ERb expression may be involved in carcinogenesis. This is further supported by the findings that ectopic expression of ERb in breast, prostate, and ovarian cancer cells inhibits motility and cell invasion and leads to increased apoptosis (Lazennec et al 2001, Cheng et al 2004.…”
Section: Introductionmentioning
confidence: 99%